2022
DOI: 10.2147/jir.s363722
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Nephritis: Current Perspectives and Moving Forward

Abstract: Lupus nephritis is a severe organ manifestation of systemic lupus erythematosus, and its pathogenesis involves complex etiology and mechanisms. Despite significant knowledge gains and extensive efforts put into understanding the development and relapsing disease activity, lupus nephritis remains a substantial cause of morbidity and mortality in lupus patients. Current therapies retain a significant unmet medical need regarding rates of complete response, preventing relapse of lupus nephritis, progression of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“… 14 31 32 It may be that current treatments reduce disease activity but do not alter the underlying pathophysiologic mechanisms of the disease and, therefore, its progression. 33 34 In this context, new treatments or better implementation of available treatment strategies are needed, especially for patients with more severe or frequently relapsing disease. Data from recent trials of add-on therapies in LN have shown favourable short-term results in terms of remission and relapse, but their potential role in DM remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“… 14 31 32 It may be that current treatments reduce disease activity but do not alter the underlying pathophysiologic mechanisms of the disease and, therefore, its progression. 33 34 In this context, new treatments or better implementation of available treatment strategies are needed, especially for patients with more severe or frequently relapsing disease. Data from recent trials of add-on therapies in LN have shown favourable short-term results in terms of remission and relapse, but their potential role in DM remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…LN is usually accompanied by elevated anti-dsDNA antibodies and anti-nuclear antibodies (ANAs) as well as signs of renal insufficiency [26][27][28]. Therefore, we detected urinary protein concentrations and the above two serum indicators at 4, 6, 10, and 12 weeks in LN mice.…”
Section: Biochemical and Pathological Alterations Of Ln Micementioning
confidence: 97%
“…Conversely, in the absence of timely and standardized therapeutic interventions, renal function typically undergoes progressive deterioration, culminating in recurrent episodes and a markedly heightened mortality rate. The precise pathogenesis leading to LN is currently uncertain, but it is unequivocally established that aberrations in cell death and cellular debris clearance, augmented nucleic acid recognition and interferon signaling, genetic anomalies, lymphocytic dysregulation, aberrant complement system activation, and perturbed cytokine milieu collectively contribute to the initiation and progression of both SLE and LN ( Lichtnekert et al, 2022 ). It has been suggested that augmented programmed cell death and impaired neutrophil-specific clearance of apoptotic remnants, resulting in the breakdown of immune tolerance to nuclear autoantigens, may constitute the incipient trigger for systemic autoimmunity in SLE ( Yang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%